ผลกระทบของการเปิดเสรีทางการค้าของประเทศไทยภายใต้ความตกลงทั่วไปว่าด้วยการค้าบริการที่มีต่อบริการด้านการบัญชีและสอบบัญชี - ชื่นจิต ชื่อลือชา (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The thesis is focused on the impacts of the General Agreement on Trade in Services on Accounting and Auditing Services. Thailand has to fulfill GATS requirements and Disciplines on Domestic Regulation in Accountancy Sector. The problem is what are the opinions of accounting profession about the effects of liberalization when professional service liberalization is effective in Thailand. For the objectives of the study, both mail questionnaire and personal interview are used in the process of gathering information. Population is composed of 4 groups: group 1 - authorized person, group 2 academician, group 3 auditing profession and group 4 accounting profession. As a result of the research, for Licensing Procedures, group 1 authorized person agree that the procedures are suitable for liberalization but the others disagree. For Qualification requirements, all groups except group 1 have opinion that they should be reviewed and amended some qualification requirements in the Auditor Act B.E. 2505. For Qualification procedures, all groups except group 2 acedemician agree that qualifying examination is efficient. For Domestic regulations and Accounting and Auditing Education, all groups agree that both regulations and education would be effected by GATS.